AN ATTEMPT AT LEGAL REGULATION OF AMBITUS (CANVASSING BEFORE ROMAN ELECTIONS) IN THE PERIOD OF THE ROMAN REPUBLIC - Deretić, Nataša Lj; Milutin, Milan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The emergence of pre-election canvassing, for which the Roman state had a special term – ambitus – has outlived centuries, so that we find this phenomenon even today. We shall here try to answer the question as to whether the campaigning before elections is a type of corruption after analyzing laws dating from the period of the Roman Republic. Defining ambitus is no easy task. A very broad definition would define it as the use of illegal methods to persuade a voter to vote for a particular candidate. This definition applies to the entire period of the Republic, and even later, to the end of the Roman history. In an attempt to understand the meaning of ambitus, it is not completely clear what means are illegal. Is it recruiting voters, blackmailing, bribing, giving presents, rendering or promising favours, organizing free feasts, staging public games, etc.? What was the punishment? Who could be punished? These things varied both during the period of the Republic and throughout the entire Roman history.